2011
DOI: 10.1017/s0317167100012415
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predictive of Obliteration After Arteriovenous Malformation Radiosurgery

Abstract: Intracranial arteriovenous malformations (AVMs) are congenital lesions consisting of focal areas of abnormal dilated arteries and veins within the brain parenchyma. Small arterioles within the AVM have an absent smooth muscle layer and lack a capillary bed 1 . This results in arteriovenous shunting through one or more fistulae. This direct shunting leads to a risk of venous rupture due to the high pressures involved with potentially devastating consequences 2 . The prevalence of intracranial arteriovenous malf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
5
0
3
Order By: Relevance
“…Publications indicate that AVM obliteration rates after a single procedure range from 70% to 80% over 5 years in selected groups, depending on AVM volume, dose delivered, location, and patient age. 1,5,6,8,13,19,25,29,33,35 The median time until MRI documentation of total obliteration of AVMs after Gamma Knife SRS (Elekta AB) has been shown to be 36 months. 16…”
mentioning
confidence: 99%
“…Publications indicate that AVM obliteration rates after a single procedure range from 70% to 80% over 5 years in selected groups, depending on AVM volume, dose delivered, location, and patient age. 1,5,6,8,13,19,25,29,33,35 The median time until MRI documentation of total obliteration of AVMs after Gamma Knife SRS (Elekta AB) has been shown to be 36 months. 16…”
mentioning
confidence: 99%
“…In addition, some studies have reported on factors that affect complete obliteration after GKRS. Since AVM is a vascular disease, studies on hemodynamic factors, particularly angiographic features, have also been published [9,10,12]. Zipfel et al [13] reported that a diffuse type nidus was a risk factor for incomplete obliteration.…”
Section: Discussionmentioning
confidence: 99%
“…As research progressed, GKRS was established as an effective treatment modality for AVM [6][7][8]. Subsequent studies also reported on factors that contribute to favorable GKRS outcomes in AVM [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of dose to the periphery of the AVM was demonstrated by Herbert et al who found that dose to the PTV margin >20Gy was strongly associated with nidus obliteration [14]. Because the incidence of symptomatic brain injury correlates with dose to surrounding NT, plan conformity is of the utmost importance.…”
Section: Discussionmentioning
confidence: 99%